Assessment Of Direct Writing In ESL Classrooms In Selected Malaysian Secondary Schools - Othman, Normah (2006)
The main aim of the present study was to investigate the use of classroom-based assessment procedures to test the efficacy of three scoring methods. The three scoring methods were tested on the scoring of direct writing. To obtain the data three phases of study were conducted in this research. The first phase was a survey research, the second phase was a correlational research, and the third phase was an ethnographic research. Each phase employed different methods of obtaining data. The results of the first phase showed that Malaysian ESL teachers who responded to the open form questionnaire did not refer to any specific scoring method for classroom assessment of guided writing, summary writing and continuous writing. Their main reference was the scoring method adopted from the Malaysian Examinations Syndicate, which was meant for the nationally standardised SPM Examination. The correlational research conducted in the second phase of the present study showed that there was a positive relationship of scores obtained from the 45 ESL teachers who used the three scoring methods to assess the three types of students' direct writing with the scores obtained from six expert raters. Apart from that the strengths and weaknesses of the scoring methods as verbalised by the 45 ESL teachers while they were assessing the writing samples, showed that each scoring method used had its own unique features for classroom assessment of direct writing. The results of the ethnographic research conducted in the third phase showed that all three ESL teachers who referred to three different scoring methods gave corrective feedback to their students. There was no significant difference in the effectiveness of the written feedback and feedback lessons given by these teachers. Students who responded to the questionnaire found that their teachers' feedback lessons had their own uniqueness depending on the scoring methods used. The findings from the third phase showed that classroom-based assessment of direct writing produced a beneficial backwash effect, for example there was a positive reaction shown by the students towards their teachers' feedback lessons.